Supreme Court Ruling on Mining Cess Karnataka Government proposal to Levy Tax: Impact on SME Industry in Iron Ore and Steel segment and Bank SME portfolio in impacted company - Suman, Saket; Choudhary, Neha (Journal of Neonatal Surgery, 2025)
On 16 th December, 2024, The Karnataka government has proposed a bill to levy tax on various minerals including Iron Ore, Bauxite, Manganese, Copper Ore etc. This is after Supreme Court (SC) ruling on 25th Jul-2024, wherein it ruled that States could collect taxes on mineral-bearing land and mineral rights w.e.f. 1st Apr-2005. Karnataka is one of the major producers of Iron Ore, accounting for 15% of India’s total Iron Ore production. In the current study, we have analysed the impact of proposed cess by Karnataka Government on major Metal & Mining companies only in case of Iron Ore. This research paper will briefly describe what will be impact on SME Industry mainly in Iron Ore and steel segment due to increase in taxes in the form of mineral bearing land. Which all are the major payer who get impacted and is there any kind of Credit at Risk at bank level. How Bank Portfolio will behave in these impacted company.